Interactive Media Application for Banana Cultivation Among Farming Groups at Rajabasa Lama 2 Village - Tama, Excellino Egi Yoga; Frimansyah, Ada Udi (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This research project aims to develop an interactive media application to enhance the knowledge and skills of banana cultivation among farming groups in Rajabasa Lama 2 Village. The development approach utilized the MDLC (Multimedia Development Life Cycle) method, with a specific focus on the implementation phase. The application has been meticulously designed to facilitate effective learning and tailored to the specific needs of the local farming community. The results of the implementation phase have demonstrated a positive impact on both productivity and the understanding of banana cultivation within the farming groups. Consequently, this application makes a valuable contribution to the advancement of sustainable agriculture at the village level.